2021
DOI: 10.3390/land10111222
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Risk Networks of Cultivated Land Protection: An Exploratory Stakeholder-Oriented Case Study in Xiliuhe Town, Hubei Province, China

Abstract: The protection of cultivated land plays an important role in ensuring food security, maintaining social stability, and promoting economic development. The protection of cultivated land involves a range of stakeholders (e.g., governments at different levels, farmers, and land-use organizations) and entails intertwined risk factors (e.g., to economic, environmental, social, and political factors). Therefore, it is crucial to identify and assess key stakeholders and associated risks to better align land protectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 137 publications
(140 reference statements)
0
0
0
Order By: Relevance
“…Li et al (2008) analyzed the carbon emission effect of land use change in Jiangsu Province, and the results showed that the expansion of built-up land may attract industrial activity with a high density of energy consumption. In the governance strategies of land expropriation, the researches mainly focus on the mechanism of economic compensation and peasants' cognition of land expropriation (Shukla and Tiwari, 2022;Cao et al, 2018;Liu et al, 2019), the land ecological protection, development right and protection policy (Nyantakyi-Frimpong, 2020) and using game theory (Hui and Bao, 2013;Tan and Tu, 2009), public choice theory (Qiu, 2007), principal-agent theory (Guo and Wu, 2008), land property rights theory (Wang et al, 2017) and other relevant theories analyze the behavior of land expropriation. Liu et al (2015) analyzed the micro-family influencing factors of peasants' choice to safeguard their rights.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al (2008) analyzed the carbon emission effect of land use change in Jiangsu Province, and the results showed that the expansion of built-up land may attract industrial activity with a high density of energy consumption. In the governance strategies of land expropriation, the researches mainly focus on the mechanism of economic compensation and peasants' cognition of land expropriation (Shukla and Tiwari, 2022;Cao et al, 2018;Liu et al, 2019), the land ecological protection, development right and protection policy (Nyantakyi-Frimpong, 2020) and using game theory (Hui and Bao, 2013;Tan and Tu, 2009), public choice theory (Qiu, 2007), principal-agent theory (Guo and Wu, 2008), land property rights theory (Wang et al, 2017) and other relevant theories analyze the behavior of land expropriation. Liu et al (2015) analyzed the micro-family influencing factors of peasants' choice to safeguard their rights.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are long-held critiques of the deficiencies in planning engagement practices, and the scope of these has ballooned as we come to consider not just whose voices are included today but also the rights and needs of future generations. As the article by Guo et al illustrates on the key stakeholders and risk factors for the cultivation of protected land in Hubei province, China, the need to mediate across diverse interests is equally a concern for rural land use governance [13]. In countries with Indigenous populations that have faced colonialism, dispossession and displacement, land use governance must address the rights to land and the self-determination of Indigenous peoples.…”
Section: Concepts and Themes In Land Use Governancementioning
confidence: 99%
“…Relevant studies in China can be summarized as follows: In terms of research content, early studies mainly explored the causes [5], types [6], and countermeasures [7] of land contract disputes. As for the causes, it is widely believed that land appreciation is the most fundamental reason.…”
Section: Introductionmentioning
confidence: 99%